2010
DOI: 10.1063/1.3530447
|View full text |Cite
|
Sign up to set email alerts
|

Top-emitting organic light-emitting diodes: Influence of cavity design

Abstract: We report on red top-emitting organic light-emitting diode structures with higher order cavities. The emission zone is placed in the first, second, and third antinodes of the electric field in the cavity by increasing the hole transport layer thickness. Furthermore, the thicknesses of the cathode and the capping layer are varied to achieve high efficiencies. Using doped charge transport layers and a phosphorescent emitter, we reach up to 29%, 17%, and 12% external quantum efficiencies for first, second, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
80
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 21 publications
1
80
0
Order By: Relevance
“…The planar topemitting OLED (Device A) reaches 15 % EQE at low current density. This value is comparable to literature reports on the most efficient single-color top-emitting OLEDs operating in the second optical maximum [3]. Compared to the planar reference, Device B (Λ B, mask = 1.0 µm) shows an enhanced EQE over the entire current range investigated.…”
Section: Performance Of Top-emitting Oleds On Periodically Corrugatedsupporting
confidence: 75%
See 2 more Smart Citations
“…The planar topemitting OLED (Device A) reaches 15 % EQE at low current density. This value is comparable to literature reports on the most efficient single-color top-emitting OLEDs operating in the second optical maximum [3]. Compared to the planar reference, Device B (Λ B, mask = 1.0 µm) shows an enhanced EQE over the entire current range investigated.…”
Section: Performance Of Top-emitting Oleds On Periodically Corrugatedsupporting
confidence: 75%
“…However, even for OLEDs with an internal quantum efficiency of nearly 100 % [6], the maximum external quantum efficiency achieved up to now for a planar device layout without light outcoupling structure is only approximately 30 % [3]. This results from the trapping of the majority of generated light within the device, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For top-emitting OLEDs without any further outcoupling techniques, the first order optical microcavity incorporating a large SPP contribution was found to be more efficient than optical microcavities exhibiting higher order WG modes. 18,19 Lately, anisotropic emitter materials showing a preferred spatial orientation of their transition dipole moment received great attention. 15,20,21 Using such materials, the efficiency limit can be increased compared to isotropic emitters.…”
Section: 3-5mentioning
confidence: 99%
“…This enhances light outcoupling to some extent, even though it does not completely solve the problem of TIR. [10][11][12] Thomschke et al 13 demonstrated the lamination of a high refractive index microlens foil on top of a white OLED and obtained a device efficacy of over 30 lm/W (27% EQE). Recently, Kim et al achieved an EQE of 44.7% (1.8-fold enhancement) for a green top-emitting OLED using a microlens array that was fabricated by evaporating an organic capping layer through a shadow mask.…”
mentioning
confidence: 99%